A metatextual markup in the national corpus of Tuvan language: the structure and functionality - Choduraa M. Mongush (Novye Issledovaniâ Tuvy, 2016)
Creating natural language corpora helps solve a number of philological and purely linguistic problems for many languages of the peoples of Russian Federation. National corpus of Tuvan language (http://www.tuvancorpus.ru/) is one of such products jointly developed by faculty and students at two universities in Krasnoyarsk and Kyzyl.